Prevalence of Capillaria plica in Danish wild carnivores. Issue 3 (December 2018) - Petersen, Heidi H.; Nielsen, Stine T.; Larsen, Gitte; Holm, Elisabeth; Chriél, Mariann
Abstract: Capillaria plica is a parasitic nematode belonging to the family Capillariidae. The adult parasites reside in the urinary tract of wild and domestic canines. The infection is most often asymptomatic, but can cause a wide range of symptoms including urinary bladder inflammation, pollacisuria, dysuria and hematuria. Canines acquire the infection by ingesting the intermediate host, the earthworm (Lumbricidae). Epidemiological studies on C. plica infection in wildlife are few and only one previous Danish study examined the prevalence in red foxes, while studies on prevalence in other animals are limited. We examined the urine sediment or urinary bladder from 375 Raccoon dogs ( Nyctereutes procyonoides ), 247 red foxes ( Vulpes vulpes ), 20 beech martens ( Martes foina ), 16 wild mink ( Neovison vison ), 14 otters ( Lutra lutra ), nine European polecats ( Mustela putorius ), three European badgers ( Meles meles ) and one golden jackal ( Canis aureus ) received as a part of Danish wildlife surveillance. Capillaria plica was detected in 73.7% of red foxes, 20.0% of beech martens, 0.5% of raccoon dogs, and in the Golden jackal. Red foxes originating from all 5 regions of Denmark were infected, although with a significantly higher prevalence in the three regions in Jutland compared to Region Zealand. Graphical abstract: Image 1 Highlights: Capillaria plica prevalence was high in Danish red foxes. Capillaria plica prevalence was low or non-existent in other wild carnivores. This study documents C. plica infection in beech martens for the first time.